Epilepsy and cannabidiol - a new perspective for seizures treatment - Ilona Kozioł; Julia Budzyńska; Magdalena Leśniewska; Joanna Milanowska (Kazimierz Wielki University, 2021)
BACKGROUND: Despite the fact that the number of antiepileptic drugs is constantly increasing, epilepsy can still be a therapeutic challenge. Approximately one-third of patients with epilepsy have persistent seizures refractory to treatment. The limited number of effective alternatives motivates researchers to seek new solutions. There is some hope for cannabidiol (CBD) preparations. AIM OF THE STUDY: The purpose of this study was to review the most recent available literature on the use of cannabidiol in the treatment of refractory epilepsy in children and adults. For this purpose, the PubMed and Google Scholar databases were reviewed. The phrase "cannabidiol and epilepsy"  was used to search the database. After Screening titles and abstracts a total of 19 papers and articles cited in them were received and analyzed in detail. RESULTS:  Nowadays there are many CBD related products available in the market, Cannabis sativa and Cannabis indica are the plants used due to their strong therapeutic effects and also seizure control. Regulations regarding the use of raw marijuana, cannabis extracts, and cannabinoid-based drugs vary from place to place. Many studies have been generated on the efficacy of cannabinoid therapy in the treatment of epilepsy. This therapy in patients with Dravet syndrome and Lennox-Gaust syndrome results in a reduction in the frequency of motor and total seizures. The most commonly reported side effects of CBD are drowsiness, seizures and diarrhea, but the therapy is generally well tolerated. SUMMARY AND CONCLUSIONS: Many available studies support the efficacy of CBD as a treatment option to reduce seizure frequency in children with drug-resistant epilepsy, particularly in patients with Dravet and Lennox-Gastaut syndrome. However, there is a lack of reports on the use of CBD in the adult population, which may be an area for further research.